Autobiography: Beginning and Evolution - Khan, Muhammad Kareem Nawaz; Kamal, Muhammad Ashraf (sourcecoder, 2023)
Autobiography is an important literary genre, in which the writer describes the social, economic, political, and social conditions of his time in addition to describing his life. However, it is important that the author records the situation according to his own thoughts and ideas, so the circumstances and events of his era can be understood, but it does not get the status of research based history. This article discusses the history, beginnings and evolution of autobiography and attempts to understand what characteristics exist in the art of autobiography in different regions of the world and how they have changed over the time. Apart from other languages, the beginning and evolution of autobiography in Urdu has also been described.